Prospek dan Kendala Pengembangan Agribisnis Jagung di Propinsi Nusa Tenggara Barat - Winarso, Bambang (Jurnal Penelitian Pertanian Terapan, 2012)
Nationally, corn demand in Indonesia is still experiencing a lot of shortcomings, so as to fulfill domestic demand is still much imports. It makes a significant opportunity for potential regions such as West Nusa Tenggara Province to develop commodity massively. As it is known that in the development of commodity corn farming will always be included in the networking activities of agribusiness commodities themselves, which means success in improving the cultivation of corn farming can not be separated from the system of agribusiness commodities.. Development of corn by most farmers are not necessarily for their own consumption but geared to meet market needs. This paper is a portrait of the problems and opportunities faced by actors from the business development of corn producers (farmers) to the consumer of corn in the region of West Nusa Tenggara Province. Through the SWOT method to try to put hail research in the field. From the results showed that the cultivation of corn farming development in the province of West Nusa Tenggara are still many obstacles and barriers. On the other hand is very promising prospects for future development Keywords: Prospect, Constraints, Agricultural Development , Corn